Facilitating the transportation of highly viscous oil by aqueous foam injection. (1st September 2019) - Jing, Jiaqiang; Sun, Jie; Huang, Hongbing; Zhang, Ming; Wang, Chunsheng; Xue, Xingchang; Ullmann, Amos; Brauner, Neima
Highlights: A new idea for cold transportation of heavy oil by aqueous foam was proposed. New hydraulic models for foam-oil horizontal pipe flow were established. Critical input foam fraction ranges for the maximum drag reduction ratio were obtained. Optimum core-to-pipe radius ratio ranges for the highest oil-transport operational coefficient were identified. Abstract: This work aims at studying a new idea for cold transportation of high-viscosity oil by foam injection. Special attention is paid to the drag reduction achieved by introducing a non-Newtonian aqueous foam to Newtonian oil in the stratified and core annular flow (CAF) regimes. Pressure gradients were measured during the co-current flow of highly viscous oil and foam in a horizontal rough-wall tempered borosilicate glass pipe with 25 m in total length and 25 mm inner diameter. Measurements were made for oil and foam superficial velocities in the range of 0.1–0.9 m/s and 0.05–0.84 m/s, respectively. New hydraulic models for foam-oil horizontal pipe flow based on the one-dimensional two-fluid approach were established. These models are capable of representing the observed flow configurations ranging from stratified flow to concentric CAF and eccentric CAF. Good agreement was obtained between the predictions and experimental data over a wide range of operating conditions. A maximum drag reduction ratio could be reached at the critical input foam-to-oil flow ratio, where complete encapsulation of the oil core by the foam becomes feasible. An optimum core-to-pipe radius ratio range for the highest oil-transport operational coefficient was identified.